Genetic Resistance to Malaria Is Associated With Greater Enhancement of Immunoglobulin (Ig)M Than IgG Responses to a Broad Array of Plasmodium falciparum Antigens. (26th August 2015) - Arama, Charles; Skinner, Jeff; Doumtabe, Didier; Portugal, Silvia; Tran, Tuan M.; Jain, Aarti; Traore, Boubacar; Doumbo, Ogobara K.; Davies, David Huw; Troye-Blomberg, Marita; Dolo, Amagana; Felgner, Philip L.; et al.
Abstract : The breadth and magnitude of P. falciparum -specific IgM and IgG responses are greater in the malaria-resistant Fulani versus the malaria-susceptible Dogon, and P. falciparum -specific IgM responses more strongly distinguish the two ethnic groups. Abstract: Background.  People of the Fulani ethnic group are more resistant to malaria compared with genetically distinct ethnic groups, such as the Dogon people, in West Africa, and studies suggest that this resistance is mediated by enhanced antibody responses to Plasmodium falciparum antigens. However, prior studies measured antibody responses to <0.1% of P falciparum proteins, so whether the Fulani mount an enhanced and broadly reactive immunoglobulin (Ig)M and IgG response to P falciparum remains unknown. In general, little is known about the extent to which host genetics influence the overall antigen specificity of IgM and IgG responses to natural infections. Methods.  In a cross-sectional study in Mali, we collected plasma from asymptomatic, age-matched Fulani (n = 24) and Dogon (n = 22) adults with or without concurrent P falciparum infection. We probed plasma against a protein microarray containing 1087 P falciparum antigens and compared IgM and IgG profiles by ethnicity. Results.  We found that the breadth and magnitude of P falciparum -specific IgM and IgG responses were significantly higher in the malaria-resistant Fulani versus the malaria-susceptible Dogon, and, unexpectedly, P falciparum -specific IgM responses more strongly distinguished the 2 ethnic groups. Conclusions.  These findings point to an underappreciated role for IgM in protection from malaria, and they suggest that host genetics may influence the antigen specificity of IgM and IgG responses to infection.